PERFORMANCE OF SHARI’A BANKING IN INDONESIA BEFORE AND DURING THE COVID 19 PANDEMIC: ISLAMICITY PERFORMANCE INDEX APPROACH - Masyitah As Sahara; Charly Marlinda; Sri Kurnia; Rachmad Chartady (International Journal of Social Science, 2023)
This research aims to determine the performance of Islamic banks using the Islamicity Performance Index approach before and during the Covid-19 pandemic. The method used in this research is a quantitative descriptive method. The object of this research is all sharia commercial banks in Indonesia. The data for this research comes from the financial reports of Islamic commercial banks for the period 2018 - 2021. The research results show that in the profit sharing ratio before and during the pandemic, only Bank Muamalat Indonesia received a fairly good title with a percentage below 30%. The results of the zakat performance ratio show that all banks still have a bad reputation in pandemic conditions and during the pandemic. For equitable distribution ratio, only Bank Jabar Banten Syariah received a fairly good title from qard and donations, and from the labor load of Bank Muamalat, Aceh Syariah and Bukopin Syariah which was able to survive with IPI standards, while in terms of net profit only Bank Mega Syariah was able to survived the pandemic with a percentage of more than 35%. For Islamic investment vs non-Islamic investment, the entire sample of Islamic commercial banks received a very good rating. And for Islamic income vs non-Islamic income, all banks in the sample received a very good title